Bioactivity of Hydroxyapatite Produced from Sea Snail Turritella Terebra - Orman, Z.; Yucel, S.; Sahin, Y. M.; Gunduz, O.; Oktar, F. N. (POLISH ACAD SCIENCES INST PHYSICS, 2019)
In this study, hydroxyapatite was produced via mechanochemical method using the sea snail Turritella terebra as a calcium source at 1200 degrees C followed by sintering. FT-IR, SEM/EDX, BET, XRD, ICP-OES analyses were applied for complete characterization. Biodegradability test in tris-buffer solution and bioactivity tests were carried out. In vitro bioactivity tests showed hydroxyapatite formation when sample was immersed in simulated body fluid (SBF) and high rate of cell viability determined based on MTT assay after 24 hours and 7 days incubation. Degradation of the samples was evaluated via pH changes for 7 days. Results exhibited that produced hydroxyapatite has ideal pore size and properties supporting bone tissue growth and cell proliferation. Therefore, it can be a good candidate for clinical applications owing to low production cost and natural-biological origin.
Keywords: Physics